Step‐Up Synthesis of Periodic Mesoporous Organosilicas with a Tyrosine Framework and Performance in Horseradish Peroxidase Immobilization. Issue 24 (16th November 2017) - Wang, Jianqiang; Zhang, Wenqi; Gu, Changqing; Zhang, Wenpei; Zhou, Man; Wang, Zhiwei; Guo, Cheng; Sun, Linbing
Abstract: New amino‐acid‐bridged periodic mesoporous organosilicas (PMOs) were constructed by hydrolysis and condensation reactions under acid conditions in the presence of a template. The tyrosine bissilylated organic precursor (TBOS) was first prepared through a multistep reaction by using tyrosine (a natural amino acid) as the starting material. PMOs with the tyrosine framework (Tyr‐PMOs) were constructed by simultaneously using TBOS and tetraethoxysilane as complex silicon sources in the condensation process. All the Tyr‐PMOs materials were characterized by XRD, FTIR spectroscopy, N2 adsorption–desorption, TEM, SEM, and solid‐state 29 Si NMR spectroscopy to confirm the structure. The horseradish peroxidase (HRP) enzyme was first immobilized on these new Tyr‐PMOs materials. Optimal conditions for enzyme adsorption included a temperature of 40 °C, a time of 8 h, and a pH value of 7. Furthermore, the novel Tyr‐PMOs materials could store HRP for approximately 40 days and maintained the enzymatic activity, and the Tyr‐PMOs–10 % HRP with the best immobilization effect could be reused at least eight times. Abstract : Tyr'd out : Novel periodic mesoporous organosilicas with a tyrosine framework (Tyr‐PMOs) are constructed. Tyrosine units are incorporated into the framework at the same time as phenolic hydroxy groups as binding centers are introduced within the channels. A long storage time and conventional stability are found for the Tyr‐PMOs after the immobilization of horseradish peroxidase (HRP).